The Impact of Macroeconomic Policies on Income Distribution: An Empirical Study of the Philippines - Blejer, Mario I.; Guerrero, Isabel (The Review of Economics and Statistics, 1990)
Mario I. Blejer, Isabel Guerrero, The Impact of Macroeconomic Policies on Income Distribution: An Empirical Study of the Philippines, The Review of Economics and Statistics, Vol. 72, No. 3 (Aug., 1990), pp. 414-423